Chemistry Teachers Can Develop Natural Science Competences by Using Chemical Models: From Pupils as Model Assemblers to Pupils as Creators of Self-Made Models - Darinka Sikošek; Mateja Žuželj (Research Highlights in Language, Literature and Education Vol. 8, 2023)
In this research, special emphasis is given to complex competencies not only their acquisition, but rather how pupils develop them. For this purpose, a learning strategy has been developed, called learning by self-generating chemical models. Pupils learn individually on their own models, which are made from easily accessible, low-cost materials. The study involved first- year secondary school-pupils, defined as self-creators of paper- and -wire models (experimental group) and assemblers of commercial models (called the control group). The research results indicate the correctness of the defined assumption of the higher performance of model self-generators in designing and developing deeper self-knowledge, as well as in acquiring a number of generic and natural science competences. The molecules under study appeared as geometric shapes and structures, which students represented by creating paper or plasticine models in the shape of balls, known as wire models. Based on the results of statistical processing of the data, we have found out what self-creation of models (as an innovative approach) leads to better understanding and to subsequently sustained knowledge for the pupil. Additionally, it should be emphasized that students who self-generated models as opposed to those who just put the models together, often developed numerous complicated skills in the areas of problem-solving, practical competence, mathematical competence, and critical thinking abilities. The knowledge that was gained in this way was also better understood.